2020
DOI: 10.2478/cipms-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ketogenic diet on vitamin D3 and testosterone hormone in patients with diabetes mellitus type 2

Abstract: A keto diet is well-known for being a low carb diet in which the body produces ketones in the liver to be used as energy. When something high in carbs is eaten, the body will produce glucose and insulin. Glucose is the easiest molecule for the body to convert and use as energy, so it will be chosen over any other energy source. The aim of this study is to examine the effect of a ketogenic diet on type 2 diabetic patients and the effect it has on testosterone, vitamin D3, HDL, LDL levels, in comparison to non-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In some studies, additional changes were observed in metabolic indices [11,50], inflammatory markers [51], or hormones [50]. An increase in circulating vitamin D3 was reported for patients with T2D on a KD compared to a control group or patients with T2D not on a KD [53]. We noted that only one study compared the effects of a KD to another diet [51].…”
Section: Intervention Studies In Healthy Adults and Patients With T2dmentioning
confidence: 94%
See 1 more Smart Citation
“…In some studies, additional changes were observed in metabolic indices [11,50], inflammatory markers [51], or hormones [50]. An increase in circulating vitamin D3 was reported for patients with T2D on a KD compared to a control group or patients with T2D not on a KD [53]. We noted that only one study compared the effects of a KD to another diet [51].…”
Section: Intervention Studies In Healthy Adults and Patients With T2dmentioning
confidence: 94%
“…Human intervention studies that investigated the effects of KDs on vitamin D in healthy adults and patients with T2D are shown in Table 1. In total, five studies were done in healthy adults [11,[50][51][52] and one in subjects with T2D [53]. Regarding healthy participants, they were mostly obese (in three studies, only obese subjects were included), and the KD was prescribed as part of a weight-loss program [11,[50][51][52].…”
Section: Intervention Studies In Healthy Adults and Patients With T2dmentioning
confidence: 99%
“…With body mass reduction by 15.1 kg, vitamin D concentration grew by 4.2 ng/mL on average [67]. In diabetic patients on a ketogenic diet, the concentration of vitamin D was significantly higher (mean concentration 53.5 ng/mL) than in those not using a ketogenic diet (mean concentration 25.1 ng/mL) [68].…”
Section: Thyroid Function Parameters (Tsh Ft3 Ft4)mentioning
confidence: 97%